(untitled) (International Journal of Engineering and Computer Science, 2016)
Traditional websites were driven by human-edited events which lead to huge web search traffic. This paper is a survey conducted for identifying the various event detection methods which are useful for event mining. Moreover this paper also suggests an automatic system to detect events from search log data and generate storyboards where the events are arranged along a timeline. Image search log is treated as a good data resource for event mining, as search logs directly reflects people’s interests. In order to discover events from log data, an approach known as Smooth Nonnegative Matrix Factorization framework (SNMF) is used. Moreover, time factor is considered as an important element for event detection as different events develop at different time. In addition, to provide a visually appealing storyboard, each event is mapped with a set of relevant images arranged along a timeline. These relevant images are automatically generated from image search results by analyzing both local and global image content feature